Evaluation of call volume and negative emotions in emergency response system telecommunicators: a prospective, intensive longitudinal investigation - Matthew Hoang; Elizabeth Hillier; Chris Conger; Devan N. Gengler; Cody W. Welty; Candace Mayer; Patricia L. Haynes (AIMS Press, 2022)
Emergency telecommunicators are essential first responders tasked with coordinated communication within the emergency response system (ERS). Despite their exposure to significant job demands, little is known about the effect of call load or call type on emotional state within these workers. Therefore, we employed a prospective, intensive longitudinal design to examine whether emergency-eligible call volume would lead to higher intensity negative emotions post-shift when controlling for pre-shift negative emotions and a number of other work and individual factors, including work duration and night shift. A total of 47 ERS telecommunicators (dispatchers, operators, other) completed ratings over working shifts within a two-week period. Call frequency was gathered through the agency Computer-Assisted Dispatch database. Negative emotions of irritation, stress, worry, and fatigue were measured through the Visual Analogue Scale administered before and after shift. Mixed linear modeling demonstrated that telecommunicators who received more calls per hour (Estimate = 3.56, SE = 1.44, p < 0.05) and more-than-usual calls per hour (Estimate = 1.97, SE = .94, p < 0.05) had higher levels of post-shift irritability. Longer-than-usual working hours also predicted higher levels of post-shift irritability (Estimate = 1.32, SE = 0.59, p < 0.05). Call volume did not predict other negative emotions, although secondary analyses demonstrated that a larger number of chronic calls lead to greater levels of post-shift worry. ERS telecommunication agencies aiming to reduce negative emotions in workers may benefit from implementing policies and programs that target working hours, call load, and work-life balance.